Comparative Effects of Auditory Electromyographic Biofeedback for Participants Who Are Blind and Sighted. Issue 4 (August 2018) - Iguchi, Masaki; Matsubara, Masaki; Kadone, Hideki; Terasawa, Hiroko; Suzuki, Kenji
This study examined differences in auditory electromyographic biofeedback (AEB) effects between participants who were sighted and blind. Past research makes clear that AEB is effective for people who are blind, particularly because of their reported superiority in auditory processing, but no study has directly compared AEB efficacy between participants who are sighted and blind. A total of 11 participants who were sighted and 10 who were blind performed a motor task requiring 20 nonfatiguing muscle contractions at 20% maximal voluntary contraction (MVC) with or without AEB. AEB reduced the error (calculated as the absolute difference of two consecutive contractions) among both participant groups, and the error for the group without biofeedback was greater for the participants who were blind than that for the sighted participants (5.20% ± 2.05% MVC and 3.30% ± 1.26% MVC, respectively; p  < .05). This finding was consistent with subjective rating data, also indicating a trend toward greater difficulty for participants who were blind when performing without biofeedback. Moreover, the AEB/no biofeedback condition showed fewer errors for the participants who were blind than for the participants who were sighted during the last part of the task ( p  = .036), indicating that participants who were blind were better at maintaining the AEB effect. These data suggest that the poor motor performance of participants who were blind was greatly improved with AEB, suggesting important applications of AEB for assistive technologies, adapted sports, and activities of daily living.